Efektivitas Media Book Creator melalui Metode Tanya Jawab dalam Meningkatkan Kemampuan Bahasa Reseptif Anak Usia 5–6 Tahun - Nurhayati; Wathoni, Hizbul; Laras Wati, Nova (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study examines the effectiveness of Book Creator media combined with the question-and-answer method in improving the receptive language skills of children aged 5–6 years. Receptive language, which includes listening and understanding stories, is a fundamental aspect of early childhood development that requires systematic stimulation. The research was conducted in Group B of Pembina 1 Public Kindergarten, Lubuk Linggau, using Classroom Action Research (PTK) carried out in two cycles. Data were collected through observation, documentation, and interviews, and were analyzed descriptively to determine the improvement across cycles. The findings indicate a significant increase in receptive language skills after the implementation of the intervention. In the first cycle, 48% of children met the expected receptive language indicators, while in the second cycle this figure increased to 87%. The 39% improvement demonstrates that the use of Book Creator media supported by the question-and-answer method effectively enhances children’s ability to listen to and comprehend stories. These results confirm that the applied learning model successfully achieved the research objective of improving receptive language skills among children aged 5–6 years.